The Effect of Vermicomposting and NPK Fertilizer on the Growth of Bok Choy (Brassica rapa L) - Reni Marianti; Ahmad Raksun; I Wayan Merta (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
One source of nutrients that influences how a plant grows and produces is fertilizer. fertilization that is possible with both inorganic and organic fertilizers. The purpose of this study is to ascertain how the development of bok choy is impacted by vermicompost, NPK fertilizer, and their combination. Design using RAL two components with five fertilization levels each, repeated three times, such that the experimental unit employed up to 75 plants. The first factor is the dose of vermicompost organic fertilizer consisting of K 0 = 0 gr (control), K1 = 50 gr, K2 = 100 gr, K3 = 150 gr and K4 = 200 gr. The second factor is the dose of NPK fertilizer (16:16:16) consisting of N 0 = 0 gr (control), N 1 = 0.3 gr, N2 = 0.6 gr, N3 = 0.9 gr and N4 = 1.2 gr. The ANOVA test was used to evaluate the data. The findings revealed that the vermicompost treatment had no appreciable impact on the plant's height, number of leaves, leaf area, wet weight, or dry weight characteristics. The use of NPK fertilizer has a sizable influence on plant properties such as height, leaf count, leaf area, wet weight, and dry weight. Vermicompost and NPK fertilizer together have a considerable influence on the metrics of plant height, leaf count, wet weight, and dry weight.